Perbandingan Uji Sifat Fisik Serbuk Effervesent Ekstrak Bunga Telang (Clitoria Ternatea.L) - Sugiyanto Sugiyanto; Wibowo Wibowo; Dedy Prayogo (Universitas Malahayati Lampung, 2022)
ABSTRACT The telang flower plant (Clitoria ternatea.L) contains phenolic compounds, flavonoids, flavonols, glycosides and anthocyanins which have potential as antioxidants. Antioxidant compounds that are often found in telang flower plants are often used as traditional medicine in the form of drinks. Study was to identify a formula that met the requirements for physical properties based on the characteristics of the effervescent powder on the effect of variations in citric acid and tartaric acid on the effervescent powder formula of telang flower extract. This study used 3 formulas using variations of citric acid, tartaric acid and PVP as a binder. Showed that for the effervescent powder flow time of telang flower extract for F1 = 11.70 seconds, F2 = 13.52 seconds and F3 = 17.22 seconds: the time of dispersion of the effervescent powder of telang flower extract for F1 = 1.31 minutes, F2 = 1.23 minutes; The pH of the telang flower extract effervescent powder for F1=7,66, F2=7.21 and F3=6.58; the water content of the telang flower extract effervescent powder for F1=0,1471gram, F2=0,2016gram and F3=0,1857gram ; and organoleptically in the form of granule powder, light purple color, slightly sour taste. Of the research results from the 3 compositions of the formula is still suitable for use on the condition that the taste is a bit sour and can be sweetened Keywords: Telang Flower (Clitoria Ternatea.L) , Effervescent Powder Formula, Physical Properties of Effervescent Powder ABSTRAK Tanaman bunga telang (Clitoria ternatea.L) mengandung senyawa fenol, flavonoid, flavonol, glikosida dan antosianin yang berpotensi sebagai antioksidan. Senyawa antioksidan yang sering terdapat pada tanaman bunga telang sering digunakan sebagai obat tradisional dalam bentuk minuman. Penelitian ini mengidentifikasi formula yang memenuhi syarat sifat fisik berdasarkan karakteristik serbuk effervescent terhadap pengaruh variasi asam sitrat dan asam tartrat pada formula serbuk effervescent ekstrak bunga telang. Penelitian ini menggunakan 3 formula dengan menggunakan variasi asam sitrat, asam tartrat dan PVP sebagai pengikat. Penelitian menunjukkan bahwa untuk waktu alir serbuk effervescent ekstrak bunga telang untuk F1=11,70 detik, F2=13,52 detik dan F3=17,22 detik: waktu dispersi serbuk effervescent ekstrak bunga telang untuk F1=1,31menit, F2=1,23 menit; pH serbuk effervescent ekstrak bunga telang untuk F1=7,66, F2=7,21 dan F3=6,58 ;kadar air serbuk effervescent ekstrak bunga telang untuk F1=0,1471gram, F2=0,2016gram dan F3=0,1857gram; dan secara organoleptis bentuk serbuk granul, warna ungu muda, rasa agak sedikit asam. Hasil penelitian dari 3 komposisi formula tersebut masih layak digunakan dengan syarat rasa yang agak sedikit asam dapat diberikan pemanis Kata Kunci: Bunga Telang(Clitoria Ternatea.L) , Formula Serbuk Effervescent, Sifat Fisik Serbuk Effervescent